Annealing study of bismuth thin films - Oksanen, Mika (2010)
Electrical and magnetotransport properties of thin bismuth films were studied in the range of 4.2 - 295 K in applied magnetic fields up to 3.5 T. The bismuth films were deposited on mica and SiO substrates and subjected to post deposition thermal annealing in order to improve the crystal structure. Annealed films showed lower resistivities and higher magnetoresistance as compared to the non annealed samples, however, the resistivity behavior was non-metallic and the mean grain size in the films were not significantly increased. A two carrier model for magnetoresistance and Hall coefficient was used to extract carrier mobilities and concentrations from the transport data.